Porsche, Volkswagen, and CSX : cars, trains, and derivatives - Stowell, David P.; McLarty, Theron (London : SAGE Publications Ltd, 2017)
Family members knew something was very wrong when Adolf Merckle, who had guided the family holding company, VEM Vermogensverwaltung GmbH, through dozens of successful investments, left the house one afternoon in January 2009 and failed to return. That night their fears were confirmed when a German railway worker located Merckle's body near a commuter train line near his hometown of Blaubeuren, about a hundred miles west of Munich. It was no secret that the recent financial crisis had taken a toll on Merckle's investments. He was known in Germany as a savvy investor, but had lost hundreds of millions of Euros after being caught on the wrong side of a short squeeze of epic proportions involving Volkswagen stock. This was not the only large bet against that company's stock. A number of hedge funds, including Greenlight Capital, SAC Capital, Glenview Capital, Tiger Asia, and Perry Capital, lost billions of Euros in a few hours based on their large short positions in Volkswagen's stock following the news on October 26, 2008, that Porsche AG had obtained a large long synthetic position in Volkswagen stock through cash-settled options. In the next two days, this short squeeze produced a fivefold increase in Volkswagen's share price, as demand for shares from hedge funds exceeded the supply of borrowable shares.
Originally published: Stowell, D., & McLarty, T. (2009). Porsche, Volkswagen, and CSX: Cars, Trains, and Derivatives. 5-209-250. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Merckle, Adolf; VEM Vermo?gensverwaltung GmbH -- Case studies; Small business investment companies -- Management -- Germany -- Case studies; Portfolio management -- Germany -- Case studies; Hedging (Finance) -- Germany -- Case studies; Automobile industry and trade -- Germany -- Case studies